Evaluation of the financial performance of American bidding companies! - Rebecca, Korang (2012)
This research study is aimed at studying the impact of mergers and acquisitions’ financial performance in different American industries over the period of 1998 to 2011. By examining the short-term stock performances and the long term accounting performance of public listed and traded companies in US, one can examine the financial performance changes associated with the merge activities in both long and short term. Also, one can argue that post-merged performances might be different depending on the size of the bidder and method of payment.